MECHANISMS FOR COORDINATING FOREIGN POLICY STRATEGIES OF STATES WITHIN MODERN REGIONAL INTEGRATION ASSOCIATIONS - Babina, Valentyna; Kovbasiuk, Stepan; Panasiuk, Viktoriia (Public Management and Policy, 2026)
This article examines the peculiarities of coordinating the foreign policy directions of states within modern regional integration associations under conditions of international environment transformation and the intensification of global challenges. The relevance of the topic is determined by the necessity to align the national interests of member countries with the collective objectives of regional cooperation. Among the key issues identified are uneven political priorities among states, differences in levels of integration and interaction, and difficulties in developing common decisions in international policy. The purpose of the study is to identify the main instruments for coordinating foreign policy actions within integration associations and to assess their effectiveness in contemporary geopolitical conditions. Comparative, systemic, and institutional approaches were applied in the research process together with methods of political analysis, forecasting, and generalization of international practice. An examination of the activities of the European Union, ASEAN, the African Union, and MERCOSUR enabled the identification of specific features of interstate interaction models in the sphere of foreign policy. Findings demonstrate that the highest level of effectiveness is achieved through mechanisms based on institutional coherence, diplomatic dialogue, and multilevel cooperation. The obtained results indicate that regional integration structures are gradually strengthening their role in international relations by developing common positions on security, economic, and humanitarian issues. At the same time, the effectiveness of collective actions depends on political trust among participants, stability of institutional systems, and the ability to respond to changes in the international environment. The article proposes a conceptual approach to assessing the effectiveness of foreign policy interaction, encompassing institutional, strategic, communicative, security, and diplomatic components, enabling a comprehensive analysis of the degree of coordination in international decision-making and the effectiveness of joint activities among participating states. Conclusions substantiate that improving the mechanisms of foreign policy interaction is an important prerequisite for strengthening regional stability, enhancing the international influence of integration associations, and ensuring an effective response to contemporary challenges. Prospects for further research include analyzing the digitalization of diplomatic processes, developing multilateral cooperation and adapting integration models to the new conditions of global politics.